Directive Speech Acts of "Command" on Death Note TV Series - Aladdin, A. Muhammad Nurfitrah Insan; Nursidah, Nursidah; Taqdir, Taqdir (NAWA: Journal of Japanese Studies, 2024)
This study aims to describe the types of speech acts of command contained in Death Note TV Series and classify the form of location in Death Note TV Series. This research is a qualitative descriptive research. The data of this research are Japanese command sentences in drama movies. The data source of this research is Death Note TV Series episodes 1 to episode 5. Data collection was done by listening and note-taking techniques. The data analysis technique used is data collection, grouping data based on classification, analyzing the data that has been grouped and concluding the research results. The results of this study there are two types of command speech acts, namely direct command speech acts and indirect command speech acts. In the direct speech act of commands, there are 16 data and indirect speech act of commands as much as 8 data. Keywords: speech act; directive; commands